Skeletal muscle mass is associated with severe dysphagia in cancer patients. Issue 4 (27th July 2015) - Wakabayashi, Hidetaka; Matsushima, Masato; Uwano, Rimiko; Watanabe, Naoko; Oritsu, Hideyuki; Shimizu, Yoshitaka
Abstract: Background: The purpose of this study was to assess the association between skeletal muscle mass, activities of daily living (ADLs) and severe dysphagia in cancer patients. Methods: A nested case‐control study was performed in 111 consecutive cancer patients with dysphagia who were prescribed speech therapy. Skeletal muscle mass comprising the cross‐sectional area of the left and right psoas muscles was assessed via abdominal computed tomography at the third lumbar vertebral level. ADLs were evaluated by the Barthel Index. The severity of dysphagia was assessed by the Food Intake Level Scale and was characterized by non‐oral feeding or oral food intake at discharge. Univariate and logistic regression analyses were applied to examine the associations between dysphagia, skeletal muscle index (SMI) and ADLs. Results: There were 86 men and 25 women (mean age, 70 years). The mean SMI was 5.68 ± 1.74 cm 2 /m 2 in men and 4.43 ± 1.21 cm 2 /m 2 in women. The median Barthel Index score was 20. Thirty‐three patients were on non‐oral feeding at discharge. The mean SMI did not differ significantly between non‐oral feeding and oral food intake groups in t ‐test. The median Barthel Index score was lower in the non‐oral feeding group in Mann–Whitney U test. Logistic regression analysis of the severity of dysphagia adjusted for age, sex, SMI, Barthel Index score, serum albumin, cancer type and stage, and vocal cord paralysis showed that SMI was associated independently with oral food intake at discharge. Barthel Index score showed a tendency to be associated with oral food intake. Conclusions: Skeletal muscle mass is associated with severe dysphagia in cancer patients. ADLs show a tendency to be associated with severe dysphagia in cancer patients.